A Implementation of Progressive Cavity Pump (PCP) Sand Abrasive Resistance Technology at Well Q-01 of Field X, Pertamina Hulu Rokan Regional 1 : Implementation of Progressive Cavity Pump (PCP) Sand Abrasive Resistance Technology at Well Q-01 of Field X, Pertamina Hulu Rokan Regional 1 - Said Aqil, Agil (ReTII, 2025)
Well Q-01 in Field X, operated under the management of Zone 4 Pertamina Hulu Rokan (PHR) Regional 1, has encountered significant production challenges due to excessive sand production. This condition frequently leads to pump stuck incidents, resulting in considerable Loss Production Opportunity (LPO). The artificial lift system currently in use, the Electric Submersible Pump (ESP), has proven to be inefficient under abrasive fluid conditions, with an average run life of less than four months. Consequently, the well requires frequent servicing, which escalates operating expenditures and disrupts the continuity of oil production. As a strategic solution, PHR, through the Networked Collaboration for New Potential (NCNP) program initiated by Subholding Upstream (SHU), in collaboration with PT. SH, has conducted a pilot test of the Progressive Cavity Pump (PCP) equipped with Sand Abrasive Resistance technology. The PCP was selected for its ability to handle fluids with high sand content and abrasive characteristics. The implementation of PCP in Well Q-01 is expected to achieve several key outcomes: extending the run life to beyond four months, reducing the frequency of well servicing operations, lowering operational costs, and enhancing oil production performance. This initiative is anticipated to provide a more reliable artificial lift solution for sand-prone wells in Zone 4, thereby contributing to improved production stability and operational efficiency in PHR Regional 1.